2020
DOI: 10.3390/atmos11040340
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of PM2.5 and Its Impact on Inhalation Health Risk Evaluation in a City with Light Industry in Central China

Abstract: A city with light industry in China was selected for the study of the chemical characteristics of PM2.5 and to assess its impact on inhalation health risks. During the period from May 2017 to February 2018, a total of 382 PM2.5 filter samples were collected across four seasons (15–20 days for each season). The results showed that the daily average PM2.5 concentration ranged from 21 to 255 µg/m3, with an annual average of 73 ± 49 µg/m3. SO42−, NO3−, NH4+, and organic matter (OM) were the dominant components, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…They discovered a rather high respiratory health risk during the smoky haze season in Chiang Mai, Thailand based on toxicity equivalent concentrations of the PAH-bound size-fractionated particulate matters (SPMs) and inhalation cancer risk (ICR). Wang et al [ 57 ] revealed that the health risk assessment of heavy metals showed that non-carcinogenic hazards are not expected to occur, while Cr contributed the highest cancer risk in the industrial areas of China.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered a rather high respiratory health risk during the smoky haze season in Chiang Mai, Thailand based on toxicity equivalent concentrations of the PAH-bound size-fractionated particulate matters (SPMs) and inhalation cancer risk (ICR). Wang et al [ 57 ] revealed that the health risk assessment of heavy metals showed that non-carcinogenic hazards are not expected to occur, while Cr contributed the highest cancer risk in the industrial areas of China.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated concentrations of the PM 2.5 , PM 10 , NO 2 , and SO 2 pollutants in winter were primarily due to winter heating, especially the combustion of coal for heating purposes. Previous studies have found that the winter heating policy leads to higher pollution concentrations in Northern China [21,30,31]. Additionally, Zhou et al reported that during winter in China, there is a statistically significant association between air pollution and respiratory mortality in northern cities; however, such an association is not observed in southern cities of China [8].…”
Section: Temporal Fluctuations In Ambient Air Pollution and Their Cor...mentioning
confidence: 98%